O nekotorych aspektach koncepcii koordinacii i koordinacionnych sposobnostej v fiziceskom vospitanii i sportivnoj trenirovke - Bojcenko, S. D.; Karsenko, E. N.; Leonov, V. V.; Smotrickij, A. L. (Teorija i Praktika fiziceskoj Kul'tury, 2003)
An evaluation of positions of the concept of coordination and the coordination abilities in the area of the theory of physical education and sports is explained in the article. It is allowing stating, that there is enough material permitting to cross traditional and becoming dogmatic aspects of the pedagogical process of assimilation of motive skills by a person in the theory of physical education and sports training.